Factors associated with organ donation by trauma patients in Nova Scotia. Issue 1 (January 2020) - Hetherington, Alexandra; Erdogan, Mete; Cameron, Adam; Lanteigne, Sara; Beed, Stephen D.; Green, Robert S.
Abstract : BACKGROUND: Trauma patients represent a significant pool of potential organ donors (PODs), and previous research suggests that this population is underutilized for organ donation (OD). Our objective was to assess factors associated with OD in the trauma population. METHODS: We retrospectively analyzed OD in Nova Scotia over a 7-year period (2009–2016) using data from the Nova Scotia Trauma Registry and Nova Scotia Legacy of Life Donor Registry. All trauma patients who died in the hospital were included. Multiple logistic regression was used to assess factors associated with donation. We also evaluated characteristics, donation types, and reasons for nondonation among trauma PODs. RESULTS: There were 689 trauma-related deaths in all hospitals in NS during the study period, of which 39.8% (274 of 689) met the Nova Scotia Trauma Registry definition of a POD. Data on OD were available for 108 of these patients who were referred to the Legacy of Life Program. The conversion rate was 84%. Compared with nondonors, organ donors were significantly younger, had a higher Abbreviated Injury Scale head score and a lower scene Glasgow Coma Scale score, were more likely to suffer ischemia from drowning or asphyxia and to require air transport, and were less likely to have comorbidities. Regression analysis showed that donation was associated with younger age (odds ratio [OR], 0.97; 95% confidence interval [CI], 0.95–0.99) and lower Glasgow Coma Scale score at the scene (OR, 0.76; 95% CI, 0.66–0.88). Odds of donation were increased with air transport compared with land ambulance (OR, 8.27; 95% CI, 2.07–33.08) and injury within Halifax Regional Municipality compared with injury outside Halifax Regional Municipality (OR, 4.64; 95% CI, 1.42–15.10). Among the 60 referred PODs who did not donate, family refusal of consent was the most common reason (28 [46.7%] of 60). CONCLUSION: Younger age, greater severity of injury, and shorter time to tertiary care were associated with OD in trauma patients. LEVEL OF EVIDENCE: Prognostic and Epidemiological, Level III. Abstract : Supplemental digital content is available in the text.